2009
DOI: 10.1093/carcin/bgp072
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of NF- B activity by NDRG2 expression attenuates the invasive potential of highly malignant tumor cells

Abstract: Downregulation of the N-myc downstream-regulated gene 2 (NDRG2) gene is involved in the progression of aggressive forms of cancer, along with the poor prognosis of cancer patients. In the current study, we examined the effect of NDRG2 expression on the metastatic potential of HT1080 human fibrosarcoma and B16F10 murine melanoma cells in both in vitro and in vivo systems. In gelatin zymography, NDRG2 expression remarkably suppressed the matrix metalloproteinase (MMP)-9 activity and slightly inhibited MMP-2 acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
82
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(87 citation statements)
references
References 24 publications
3
82
0
2
Order By: Relevance
“…Kim et al [58] found that N-myc downstream-regulated gene 2 (NDRG2) suppressed MMP-9 expression but not MMP-2 expression in HT1080 human fibrosarcoma cells and B16F10 murine melanoma cells, and NDRG2 repressed NFκB/p65 activity but not AP-1 activity in these cells. The results obtained by Fong et al [54] revealed that simultaneous inactivation of NFκB/p65 and AP-1 suppressed MMP-2 expression in 12-O-tetradecanoylphorbol-13-acetate-treated human lung cancer A549 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Kim et al [58] found that N-myc downstream-regulated gene 2 (NDRG2) suppressed MMP-9 expression but not MMP-2 expression in HT1080 human fibrosarcoma cells and B16F10 murine melanoma cells, and NDRG2 repressed NFκB/p65 activity but not AP-1 activity in these cells. The results obtained by Fong et al [54] revealed that simultaneous inactivation of NFκB/p65 and AP-1 suppressed MMP-2 expression in 12-O-tetradecanoylphorbol-13-acetate-treated human lung cancer A549 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that NDRG2 could suppress cell proliferation through the regulation of cyclin D1 and TCF/b-catenin activity (19,20). NDRG2 was also reported to suppress NF-kB activity in order to inhibit carcinogenesis, invasion, and metastasis of human malignancy (21,22). Although the clinical role and therapeutic effect of NDRG2 are still to be investigated, the present study will continue to improve our understanding of the biological profile and behavior of CRC and enhancing prognostic stratification of patients with the aim of developing individualized new treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it is reported that NDRG2 could suppress cell proliferation possibly through the regulation of cyclin D1 and T-cell factor (TCF)/b-catenin activity (19,20). Recent study also showed that NDRG2 could suppress nuclear factor kappa B (NF-kB) activity, suggesting a possible mechanism for NDRG2 to participate in carcinogenesis and progression of human malignancy (21,22). However, to our knowledge, no correlations of NDRG2 with relapse and prognosis has not been addressed in CRC yet.…”
Section: Introductionmentioning
confidence: 99%
“…Matrigel plug assay. Subconfluent A431 cells were harvested, washed twice, and resuspended in PBS at 7.5 × 10 7 cells/mL [31]. Aliquots of the cells (0.1 mL) were mixed with 0.4 mL of growth factor-reduced Matrigel (BD Biosciences, 356231) with or without Fc or Fc-TPP11 (10 mg/kg), and the mixture was immediately injected SC, into the right thigh of nude mice.…”
Section: Pharmacokineticsmentioning
confidence: 99%